Assessing Dental Hygiene Students' and Community Caregivers' Knowledge of Strategies for Caries Prevention. Issue 3 (1st March 2019) - Bress, Lisa E.; Horowitz, Alice M.; Capobianco, Diana M.; Fleming, Deborah E.; Kleinman, Dushanka V.
Abstract : With dental caries being a common chronic disease in children and adults, oral health literacy is needed to improve oral health and prevent caries. If oral health providers themselves are confused about preventive strategies, they cannot effectively educate the public or other health care providers. The aim of this study was to assess University of Maryland dental hygiene students' understanding of and ability to communicate caries preventive strategies to low‐income populations during a community service‐learning program in 2013 and 2014. Fifty baccalaureate degree dental hygiene students were asked to complete surveys before and after receiving a presentation on caries preventive strategies and after an outreach event, and 77 low‐income caregivers were asked to complete surveys before and after receiving oral health education from the students. The key knowledge question on all surveys asked respondents to select the "single best way to prevent tooth decay" (i.e., provide caries prevention) from a list that included the following items: limit sweets, going to the dentist, brushing teeth, using fluoride toothpaste, flossing, drinking fluoridated water, fluoride varnish, and sealants. Of the 50 students, 41 completed all three surveys, for a response rate of 82%; all 77 caregivers (100%) completed the survey before the counseling session, and 37 (48%) completed the survey afterwards. While the results showed a significant knowledge increase for the students that drinking fluoridated water is the best caries prevention strategy, only 44% of them correctly ranked that option first even on the final survey, and only 8% of the caregivers ranked that option first even after counseling. These results suggested that neither the students nor the caregivers understood the benefits of community water fluoridation (CWF), even after the interventions. In spite of their low knowledge scores, it was encouraging that 86‐92% of the caregivers reported that the students demonstrated respect for them and spent an appropriate amount of time with them and that they understood the information the students communicated. In discussions after the surveys, the students reported that they had received inconsistent messages from faculty members regarding the benefits of CWF, which resulted in their confusion. These results led the authors to revise their program's instruction to increase the students' knowledge of caries prevention strategies.